Model Pengukuran Green Human Resource Management pada Perusahaan Startup di Indonesia - Adyamar Giftby Ellyolga Irwan; Rina Anindita (LITERATUS, 2022)
The increasing of environmental problems cause companies as a part of the community to also have a role in overcoming these environmental problems, one of which can be done through the implementation of Green Human Resource Management (GHRM) policies in company management. The purpose of this study is to determine the most appropriate GHRM measurement dimensions for startup companies in Indonesia and to review the extent to which the GHRM system has been implemented. The study was conducted using a questionnaire survey distributed online to 197 employees of startup companies in the Greater Jakarta area. Data were analyzed using factor analysis and descriptive analysis methods. The results show that there are five dimensions that make up green human resource management in startup companies, namely green organizational support, green management commitment, green health & safety, green employees, and implementation of green policies. Green health & safety is the most widely applied dimension to startup companies in Indonesia.